2012
DOI: 10.1111/j.1464-0597.2011.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Combating HIV/AIDS in Sub‐Saharan Africa: Effect of Introducing a Mastery Motivational Climate in a Community‐Based Programme

Abstract: The study investigated whether mastery motivational strategies could enhance the effectiveness of life skills interventions for HIV education through sport. A quasi field experimental study was conducted in Tanzania with at‐risk children (n= 564) randomly grouped into two intervention groups and one control group. The intervention groups received AIDS education using trained peer coaches in football, with one group using mastery strategies. Children in the intervention groups all reported significantly greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…Previous study in Tanzanian PE contexthas indicated that the goals orientation of the PE students influences the outcomes of participation in PE programs [13]. Thus, the present research extend further the use of the goal theory byexaminingthe gender differences in the cognitive and affective outcomes (purpose of PE, satisfaction and enjoyment)of participation in PE programs in secondary schools in Tanzania using the achievement goal approach(see [30,31,37].…”
Section: Motivational Perspectivesupporting
confidence: 54%
See 1 more Smart Citation
“…Previous study in Tanzanian PE contexthas indicated that the goals orientation of the PE students influences the outcomes of participation in PE programs [13]. Thus, the present research extend further the use of the goal theory byexaminingthe gender differences in the cognitive and affective outcomes (purpose of PE, satisfaction and enjoyment)of participation in PE programs in secondary schools in Tanzania using the achievement goal approach(see [30,31,37].…”
Section: Motivational Perspectivesupporting
confidence: 54%
“…However, understanding of these psychological outcome variables of participation requires a theoretical perspective that is culturally sensitive. For over six decades researchers have used theories of motivation in particular expectancy value, [28], self efficacy [29], and goal orientation [30,31] to understand and explain differences in motivation of individuals in PE and sport context.…”
Section: Introductionmentioning
confidence: 99%
“…Além dos artigos realizados nos Estados Unidos, [18][19][20][21][22][23][24] o HIV-K-Q foi adaptado e utilizado para avaliar o conhecimento em estudos realizados em Portugal 25 , na Argentina, 26 na Indonésia, 27 na Malásia, 28 na Índia, 29 na Nigéria, 30 na Bélgica, 31 na Coreia do Sul, 32 na Ucrânia 33 e na Tanzânia. 34 A análise do conhecimento sobre o HIV em diferentes países, com diferentes culturas e comportamentos, pode permitir futuramente um melhor controle desta doença.…”
Section: Discussionunclassified
“…Estudantes com elevada educação formal podem apresentar elevados escores. Tendo em consideração os argumentos expostos acima e a diversidade de países diferentes que utilizam o HIV-K-Q, [25][26][27][28][29][30][31][32][33][34] os autores do presente estudo escolheram a versão longa desse instrumento para ser adaptada para a cultura brasileira.…”
Section: Discussionunclassified
“…A mastery-oriented climate is one in which the standards of success and failure are measured in relation to oneself and the process of improvement is valued over the achievement of specified results. In contrast, a performance-oriented climate is one in which the standards of success and failure lie with others and a sense of competence is gained through comparison with others ( Ames, 1992 ; Maro and Roberts, 2012 ). The motivational climate is included in Achievement Goal Theory (AGT; Ames, 1992 ), which has dominated research on achievement motivation in sports and physical activity over the past 30 years ( Harwood et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%